An open trial and discontinuation study of fluoxetine in children and adolescents with obsessive-compulsive disorder - Semerci, Z. Bengi; Unal, Fatih (The Turkish Journal of Pediatrics, 2001)
The purpose of this study was to examine the efficacy and safety of fluoxetine for short-term and long-term treatment in children and adolescents with obsessive-compulsive disorder (OCD). Twenty-three children and adolescents (mean age 12.0, SD = 2.3) treated with fluoxetine for OCD with or without Gilles de la Tourette’s syndrome were the subjects of this study. The design was an open-label trial for 20 weeks of fixed-dose fluoxetine (20 mg/day). OCD symptom severity was measured with the Maudsley OCD scale and with Clinical Global Impression Scale (CGI). All of the patients were followed-up after discontinuation of the drug for 24 months. Patients with OCD showed a significant decrease in the severity of their OCD symptoms according to Maudsley OCD scores (p < 0.001) and CGI scores (p < 0.001). Fluoxetine was generally well tolerated, and side effects were relatively mild. Ten patients (43.5%) with OCD who responded to fluoxetine relapsed in the follow-up period, but responded well to fluoxetine. These results indicate that fluoxetine is effective and safe for short-term and long-term treatment of OCD in children and adolescents.